Self-monitoring blood pressure in pregnancy: evaluation of women’s experiences of the BUMP trials - Chisholm, A; Tucker, KL; Crawford, C; Green, M; Greenfield, S; Hodgkinson, J; Lavallee, L; Leeson, P; Mackillop, L; McCourt, C; Sandall, J; Wilson, H; et al. (BioMed Central, 2024)
Background: The COVID-19 pandemic accelerated the adoption of remote care, or telemedicine, in many clinical areas including maternity care. One component of remote care, the use of self-monitoring of blood pressure in pregnancy, could form a key component in post-pandemic care pathways. The BUMP trials evaluated a self-monitoring of blood pressure intervention in addition to usual care, testing whether it improved detection or control of hypertension for pregnant people at risk of hypertension or with hypertension during pregnancy. This paper reports the qualitative evaluation which aimed to understand how the intervention worked, the perspectives of participants in the trials, and, crucially, those who declined to participate. Methods: The BUMP trials were conducted between November 2018 and May 2020. Thirty-nine in-depth qualitative interviews were carried out with a diverse sample of pregnant women invited to participate in the BUMP trials across five maternity units in England. Results: Self-monitoring of blood pressure in the BUMP trials was reassuring, acceptable, and convenient and sometimes alerted women to raised BP. While empowering, taking a series of self-monitored readings also introduced uncertainty and new responsibility. Some declined to participate due to a range of concerns. In the intervention arm, the performance of the BUMP intervention may have been impacted by women’s selective or delayed reporting of raised readings and repeated testing in pursuit of normal BP readings. In the usual care arm, more women were already self-monitoring their blood pressure than expected. Conclusions: The BUMP trials did not find that among pregnant individuals at higher risk of preeclampsia, blood pressure self-monitoring with telemonitoring led to significantly earlier clinic-based detection of hypertension nor improved management of blood pressure. The findings from this study help us understand the role that self-monitoring of blood pressure can play in maternity care pathways. As maternity services consider the balance between face-to-face and remote consultations in the aftermath of the COVID-19 pandemic, these findings contribute to the evidence base needed to identify optimal, effective, and equitable approaches to self-monitoring of blood pressure.